2014
DOI: 10.1007/s12639-014-0542-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microscopic and immunoassay examination in the diagnosis of intestinal protozoa of humans in Mansoura, Egypt

Abstract: Protozoal diseases are prevalent globally and especially in developing countries that have relatively lower socioeconomic populations such as Egypt. Direct microscopic examination (DME) is used for the detection and identification of protozoa but lacks sufficient reliability, and thus may be detrimental in obtaining accurate diagnostic or epidemiological data. In this study, we determine the prevalence of infections by Giardia intestinalis, Cryptosporidium sp., and Entamoeba histolytica in humans in Egypt. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Also, prevalence of various protozoa was as follows among healthy individuals in another study from Egypt: E. histolytica 2%, G. lamblia 18%, Blastocystis hominis 10%, and Cryptosporidium 12% [24]. In Mansoura, results of the study conducted by Elswaif et al [25] revealed that the prevalence of protozoa among patients attending Mansoura University Hospital out-patient clinics presenting with diarrhea was 81% for Giardia 15% for Cryptosporidium and 14% for E. histolytica. Finally, a recent study in Egypt comprising patients complaining of diarrhea proved that Giardia was the most common parasite 30.5% as detected by microscopy while Cryptosporidium spp.…”
Section: Resultsmentioning
confidence: 89%
“…Also, prevalence of various protozoa was as follows among healthy individuals in another study from Egypt: E. histolytica 2%, G. lamblia 18%, Blastocystis hominis 10%, and Cryptosporidium 12% [24]. In Mansoura, results of the study conducted by Elswaif et al [25] revealed that the prevalence of protozoa among patients attending Mansoura University Hospital out-patient clinics presenting with diarrhea was 81% for Giardia 15% for Cryptosporidium and 14% for E. histolytica. Finally, a recent study in Egypt comprising patients complaining of diarrhea proved that Giardia was the most common parasite 30.5% as detected by microscopy while Cryptosporidium spp.…”
Section: Resultsmentioning
confidence: 89%
“…In our study, direct microscopy of fecal concentrates was used for detection and differentiation of intestinal protists, whereas a few previous studies 28,29,43,44 used a combination of or different examination and diagnostic tests, including microscopy of fecal concentrates, immunoassays, an immunofluorescence assay including 49,6-diamidine-2phenylindole-dihydrochloride, trichrome staining, and iodine staining, all of which may differ in terms of sensitivity with a consequence for the reported Giardia prevalence. This can be exemplified by a study carried out recently in Egypt, 43 where the prevalence of Giardia was 38% based on immunoassay results compared with 18% based on results from microscopy of fecal concentrates.…”
Section: Discussionmentioning
confidence: 99%
“…This laborious nature arises from the intricate processes inherent to the chosen method, where each sample mandates individual scrutiny by the professional [31]. Literature corroborates that the experience and proficiency of the professional executing the technique are pivotal, necessitating the identification of cysts, trophozoites, and eggs within biological samples laden with extraneous material that could potentially obfuscate microorganism structures [25][26][27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Light microscopy methods, renowned for their cost-effectiveness [32][33][34][35][36], harbor the added advantage of diagnosing a spectrum of intestinal parasites beyond giardiasis, including ascariasis, amoebiasis, taeniasis, and hookworm [12,34,36]. The Ritchie method emerges as the favored approach according to the data gleaned from selected articles.…”
Section: Discussionmentioning
confidence: 99%